2022
DOI: 10.3390/healthcare10112128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Patient Experience Scores and Health Insurance

Abstract: (1) Background: the patient experience may be a performance indicator in value-based reimbursement. Accordingly, providers have an incentive to understand factors that affect their patients’ experiences. This study evaluated the relationship between health insurance type and patient experience ratings. (2) Methods: individual-level demographic, health/healthcare, and patient experience data were extracted from the Full-Year Consolidated Data File of the 2019 Medical Expenditure Panel Surveys. A logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Such a correlation has been documented in the existing literature. [24][25][26] The low satisfaction of patients without health care insurance is reflective of the financial burden of these patients to afford expensive health care and decreased odds of having a regular health care provider. [24][25][26] Also, many physicians have reported that they frequently alter their clinical management based on patients' insurance status, which may lead to patient inconvenience as physicians steer away from the most efficient plan of treatment toward lessexpensive options for patients with no insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Such a correlation has been documented in the existing literature. [24][25][26] The low satisfaction of patients without health care insurance is reflective of the financial burden of these patients to afford expensive health care and decreased odds of having a regular health care provider. [24][25][26] Also, many physicians have reported that they frequently alter their clinical management based on patients' insurance status, which may lead to patient inconvenience as physicians steer away from the most efficient plan of treatment toward lessexpensive options for patients with no insurance.…”
Section: Discussionmentioning
confidence: 99%